Fabrication and properties of macroscopic carbon nanotube assemblies transforming from aligned nanotubes - Zhang, Y. N. (2015)
Macroscale assemblies of well-aligned carbon nanotubes (CNTs) can inherit intrinsic properties from individual CNTs and at the same time ease handling difficulties that occur at nanometer scale when dealing with individual CNTs. Herein, simple fabrication processes are introduced to produce a variety of macroscale CNT assemblies, including well-aligned CNT bundles, CNT films, and CNT fibers, from the same starting material: spinnable CNT arrays. The electrical and mechanical properties of the as-prepared CNT assemblies have been investigated and compared. It is found that CNT films show an electrical conductivity of 145~250 S cm−1 which is comparable to CNT fibers, but two orders magnitude higher than that of conventional Bucky paper. CNT fibers exhibit diameter dependent tensile strength which is mainly attributed to the nonuniform twisting along the radial direction of fibers.